2017
DOI: 10.1016/j.scitotenv.2017.02.184
|View full text |Cite
|
Sign up to set email alerts
|

Towards a competitive solid state fermentation: Cellulases production from coffee husk by sequential batch operation and role of microbial diversity

Abstract: The cost of cellulases is the main bottleneck for bioethanol production at commercial scale. Solid-state fermentation (SSF) is a promising technology that can potentially reduce cellulases cost by using wastes as substrates. In this work, a SSF system of 4.5L bioreactors was operated continuously by sequential batch operation using the fermented solids from one batch to inoculate the following batch. Coffee husk was used as lignocellulosic substrate. Compost was used as starter in the first batch to provide a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
48
0
3

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
3
2

Relationship

2
7

Authors

Journals

citations
Cited by 67 publications
(51 citation statements)
references
References 58 publications
0
48
0
3
Order By: Relevance
“…Spouted bed bioreactor show improved fermentation performance, including higher product titers, yields, and productivity [124]. They studied the spouted-bed bioreactor with intermittent spouting with air, which achieved high production levels both of total protein and enzymes.…”
Section: Spouted-bed Bioreactorsmentioning
confidence: 99%
See 1 more Smart Citation
“…Spouted bed bioreactor show improved fermentation performance, including higher product titers, yields, and productivity [124]. They studied the spouted-bed bioreactor with intermittent spouting with air, which achieved high production levels both of total protein and enzymes.…”
Section: Spouted-bed Bioreactorsmentioning
confidence: 99%
“…The result was similar to packed-bed bioreactor, but spouted-bed had uniformity and had no solids-handling problems. However, it was found that continual spouting was found to be unfavourable to this SSF, possibly because of shear impact damage to fungal mycelium during spouting [124]. The design scheme of the spouted-bed bioreactor is illustrated in Figure 7.…”
Section: Spouted-bed Bioreactorsmentioning
confidence: 99%
“…Cellulases and xylanases' production is mainly associated with microorganisms that are able to fully degrade lignocellulosic materials; it is, therefore, is of great relevance to determine the most-adequate strain or specialized inoculum to enhance cellulase production [11]. In this context, several inoculation strategies have been proposed for the production of different enzymatic compounds; they include the use of autochthonous microbiota for protease production [12], development of a specialized mixed consortium [13], and the use of specific cellulose-producing strains (mainly fungi) such as Trichoderma reseei [14][15][16][17][18]. T. reseei is a widely-referred to fungus for cellulase production using agroindustrial or agricultural wastes with a significant fibre content (cellulose > 25%) as substrates [13].…”
Section: Introductionmentioning
confidence: 99%
“…Another interesting alternative to be assessed is the development of different operational strategies such as working in a sequential batch configuration thus allowing the adaptation of the autochthonous microbiome as reported by Cerda et al (2017a). Another approach would be to work with specific strains to overproduce, by instance, proteases, as successfully reported by El-Bakry et al (2016).…”
Section: Hydrolytic Enzymes Productionmentioning
confidence: 99%